Pengaruh Struktur Kepemilikan dan Growth Opportunity terhadap Dividend Payout Ratio - Nur Aisah; Anwar Hariyono (JIATAX (Journal of Islamic Accounting and Tax), 2020)
This study aims to analyze the effect of the variable structure of ownership (managerial ownership, institutional ownership, and concentration of ownership) and growth opportunity on the dividend payout ratio. With profitability, firm size, and leverage as control variables. This research uses a quantitative approach with secondary data types. The research population is a non-financial company listed on the Indonesia Stock Exchange, which is then processed using a purposive sampling method based on certain criteria. From the specified criteria obtained a sample of 36 companies. This research uses multiple linear regression. Regression results show that managerial ownership, institutional ownership, ownership concentration, and size do not significant effect on dividend payout ratio. Growth Opportunity has a negative and significant effect on dividend payout ratio. Profitability that is proxied by ROA and leverage proxied by DER has a positive effect on the dividend payout ratio.